Del Gabinete Científico al Aprendizaje Interactivo: el Museo Alfredo Dugès - Ramírez Moreno, Sara Eréndira; Estrada, Salvador; Magaña-Cota, Gloria Eugenia (Acta Universitaria, 2012)
A case study is presented which illustrates the strategies employed by a university sponsored natural science museum in meeting the challenge posed by the “hands-on” model in its efforts to bring scientific knowledge to the general public. The extent to which a series of actions are learned, assisted by the attraction that the opportunity to touch provides, is evaluated. The strategies employed are aligned to the general school curriculum and seek to be effective in attracting newcomers to the world of science. Such strategies provide for increased museum attendance, whilst enriching the learning process and enhancing the public’s understanding and appreciation of scientific and technological advances. They also offer a range of experiences to encourage involvement in scientific activity. Furthermore, we take a brief look at the challenge of developing activities aimed at creating a loyal and permanent public with a concrete interest in science in general and the natural sciences in particular.
Keywords: Array; Array; Array; Array